Indian economics - "Dewett, Kewal Krishan" (New Delhi, 1974)
This book covers the following topics Development and planning; Natural and human resources; Structure and problems of Indian agriculture; Problems of Indian Industry and Industrial labour; Transport and Foreign Trade ; Currency system price and banking and Income, Employment and Public finance etc
Keywords: Economics